2006
DOI: 10.1111/j.1574-6968.1997.tb10177.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable xylanases produced at 37°C and 45°C by a thermotolerant Aspergillus strain

Abstract: Differences between xylanases produced by Aspergillus FP-470 growing under normal (37 degrees C) and temperature stress conditions (45 degrees C) were evaluated. Fungal growth at 45 degrees C was seriously affected. However, the xylanase specific activity was 2.5 times higher than that produced at 37 degrees C. Optimum pH and temperature were 6.5, 80 degrees C and 4.3, 50 degrees C for the xylanases produced at 37 degrees C and 45 degrees C, respectively. Electrophoresis showed that a more complex xylanolytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
2
4
0
3
Order By: Relevance
“…4A). Similar results were reported by Khasin et al (1993) for Bacillus steathermophilus T6 xylanases and by Mendicuti-Castro et al (1997) for Aspergillus strain xylanases. When the xylanase was preincubated at different times (0-75 min) at various temperatures (Fig.…”
Section: Properties and Partial Purification Of The Xylanases Producesupporting
confidence: 91%
“…4A). Similar results were reported by Khasin et al (1993) for Bacillus steathermophilus T6 xylanases and by Mendicuti-Castro et al (1997) for Aspergillus strain xylanases. When the xylanase was preincubated at different times (0-75 min) at various temperatures (Fig.…”
Section: Properties and Partial Purification Of The Xylanases Producesupporting
confidence: 91%
“…A change in the intrinsic properties of the xylanase from Aspergillus FP-470 was also reported by Mendicuti-Castro [12]. In that case, a change from 37°C to 45°C resulted in a switch of optimum pH from 6.5 to 4.3 and a switch of temperature optimum from 80°C to 50°C.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, A. terreus bioactivities recorded as 14.9 and 26.5 lg/ml against V. ordalli and V. angularuim respectively, showed a wide tolerance of temperature above 30°C. Comparing with these results, the optimum temperature for the marine V. ramulosa was ranged from 24-26°C with maximum productivity of 6.2 lg/ml [17]. Vishwanatha et al [30] showed the culture flasks of A. oryzae MTCC 5341 for maximum acid protease production at Fig.…”
Section: Effect Of Ph and Temperature On The Productivitymentioning
confidence: 71%
“…The filtrate of the precultured A. terreus was divided into five portions and exposed separately to different temperature degrees (30, 40, 60, 80 and 100°C) for 30 min. The thermo-stability was assessed as a function of their bioactivity against the tested pathogens [17].…”
Section: Thermo-stability Testmentioning
confidence: 99%